LncRNA landscape and associated ceRNA network in placental villus of unexplained recurrent spontaneous abortion - Minyue Tang; Qingfang Li; Shan Wan; Qingqing Chen; Shujun Feng; Jiali You; Wei Wang; Yimin Zhu (BMC, 2023)
Abstract Background Unexplained recurrent spontaneous abortion (URSA) is one of the most challenging conditions frustrates women of childbearing age profoundly. The gene expression patterns and biological characteristics of placental villus in patients with URSA remain largely unknown. The aim of our study was to identify potential lncRNAs as well as their action mechanisms in URSA. Method The ceRNA microarray was used to identify the mRNA and lncRNA expression profiles of URSA patients and normal pregnancy. Functional enrichment analyses for differentially expressed mRNAs in URSA were performed. Protein-protein interaction analysis of differentially expressed mRNAs was performed to identify hub genes and key modules. Subsequently, the co-dysregulated ceRNA network of URSA was established, and the enrichment analyses for the mRNAs in the ceRNA network was implemented. qRT-PCR was performed to validated the expression of key ENST00000429019 and mRNAs in URSA. Results We found that URSA placental villus have distinct mRNA and lncRNA expression profiles through ceRNA microarray, with a total of 347 mRNAs and 361 lncRNAs differentially expressed compared with controls. The functional enrichment analysis revealed that ncRNA processing, DNA replication, cell cycle, apoptosis, cytokine-mediated signaling pathway, ECM-receptor interaction were the potentially disrupted pathways in URSA patients. Then we constructed a co-dysregulated ceRNA network and found differentially expressed mRNAs were regulated by a small fraction of hub lncRNAs. Finally, we found a key network of ENST00000429019 and three cell proliferation or apoptosis related key mRNAs (CDCA3, KIFC1, NCAPH), and validated their expression and regulation in tissue and cellular levels. Conclusions This study identified a key ceRNA network, which might take part in URSA and correlate with cell proliferation and apoptosis. Optimistically, this study may deepen our apprehensions about the underlying molecular and biological causes of URSA and provide an important theoretical basis for future therapeutic strategies for patients with URSA.